Color image Steganography Based on Artificial DNA Computing - Al-Iedani, Najat Hameed Qasim; Almola, Sahera A. S. (Informatica, 2023)
Modern genetic engineering developments have made it possible for artificial DNA strands to be included in living cells of creatures. Many methods of artificial insertion have been developed using DNA, which has excellent data storage capacity. Most of these techniques are used to encode text data, while there has been little research on encoding other types of media. Methods for encoding images have very little studied, and most of them are dedicated to black-and-white images. The proposed method focuses on encoding a secret color image and then embedding it in another color image, this comprises two levels of security. The first level is provided by converting binary color images into DNA sequences. A second level is provided by embedding the bits of DNA sequence into LSBs of the cover image to generate the stego image. Extraction process is in the reverse procedure. The proposed method is significantly efficient, according to the experimental results.